Education and empowerment of young women in the prevention of anemia through the consumption of green bean juice and soy milk in the school environment - Adi Elviana Baunsele; Fenni Valianda A. Ramadhan; Fanni Hanifa (Abdimas Polsaka, 2026)
Anemia remains a persistent public health problem among adolescent girls, significantly affecting their growth, learning capacity, and overall quality of life. This community-based study aimed to evaluate the effects of mung bean extract and soy milk consumption on hemoglobin (Hb) levels among adolescent girls suffering from moderate anemia. The activity was conducted as part of a community health service program focused on improving nutritional awareness and reducing anemia prevalence through affordable local food sources. The intervention involved two adolescent participants with confirmed moderate anemia. One participant consumed mung bean extract, while the other consumed soy milk, each 250 ml twice daily for seven consecutive days. Hemoglobin levels were measured before and after the intervention using a portable hemoglobinometer. The results showed a substantial improvement in Hb concentration for both participants: the mung bean group experienced a 1.3 g/dL increase, and the soy milk group a 1.4 g/dL increase. Both participants reported reduced fatigue, improved concentration, and enhanced general well-being. These findings suggest that plant-based iron sources, such as mung beans and soy milk, are effective and affordable alternatives to conventional supplementation for managing anemia among adolescents. Furthermore, integrating such nutritional education into community outreach programs can raise awareness of balanced diets and iron-rich local foods. This initiative demonstrates that simple, sustainable dietary interventions can significantly contribute to improving adolescent health in the community